READING CORNER AS A MEANS OF INSTILLING CHARACTER VALUES AT AL-FALAH BOARDING SCHOOL - Noveria Anggraeni Fiaji; Muhammad Hambali; Trisna Andarwulan; Prima Zulvarina (Wisesa: Jurnal Pengabdian Masyarakat, 2023)
Al Falah Islamic Boarding School was founded in 1989 as one of the first Muhammadiyah Islamic Boarding Schools in Gorontalo consisting of Madrasah Tsanawiyah and Madrasah Aliyah. Based on data on daily activities carried out at the Al Falah Islamic Boarding School, it is still not visible that there are maximum literacy activities held every day, of course this has more or less had an impact on the scientific level of Al Falah students because literacy is one of the basic foundations of an educational activity. Good literacy activities can have an impact on good academic achievement and awareness of education. Literacy activities must of course implement a good system in all aspects of the activity, not least of which must be supported by adequate facilities. However, facilities in the form of infrastructure, especially reading books or other educational supporting books, are not yet fully available in the Al Falah library. This should be used as one of the Islamic boarding school's superior programs and as a culture that must be continuously developed and renewed. As a solution, community service was carried out using socialization method to the ustadz and ustadzah caretakers of the Al-Falah Islamic Boarding School to create a reading corner program as a means of literacy for students at Al Falah Islamic Boarding School. Not only reading corners, other literacy methods have also been designed in this community service program.